Hyper Infection of Strongyloides Stercoralis Associated With Secondary Bacterial Pneumonia in a Malnourished Patient - Nayakanti, Raghu Prakash Reddy; Motati, Rama Kesava Reddy; Muneppagari, Nettikantaiah; Mudhaliar, Mohanraj Rathinavelu (Indian Journal of Pharmacy Practice)
Strongyloides stercoralis, an intestinal nematode is more prevalent in the tropics or subtropics. Hyper infection syndrome in immuno competent patients is due to asymptomatic infections, increased parasite number, dissemination and it leads to death if unnoticed. Use of corticosteroids, HIV, HTLV-1, malignancies and malnutrition are predisposing factors for hyper infection. Secondary bacterial infections are known to cause increased mortality in these patients in antibiotic resistant era. Here we report a case of strongyloides hyper infection syndrome associated with secondary bacterial pneumonia in a malnourished female patient.
Keywords: Hyper infection syndrome; Immune compromised; Malnourished; Pneumonia; Strongyloides stercoralis